Structural, magnetic and dielectric properties of vanadium substituted four layered Aurivillius Bi5FeTi3O15 ceramics. Issue 15 (15th October 2019) - Prajapat, Deepak; Sagdeo, Archna; Reddy, V. Raghavendra
Abstract: The present work reports the study of four layer Aurivillius compound Bi5 FeTi3 O15 (BFTO) with V 5+ (≤50%) doping at B-site ( F e 3 +, T i 4 + ). This is considered to be equivalent of increasing the magnetic ion F e 3 + concentration from 25% to 37.5%. Phase purity of the samples is confirmed with lab and synchrotron based x-ray diffraction measurements. The temperature dependent magnetization measurements indicate the paramagnetic nature of BFTO down to 2 K and the development of long-range antiferromagnetic (AFM) ordering with V 5+ doping. It is observed that the AFM Néel transition temperature T N decreases with increase of V 5+ doping. The presence of iron oxide impurity phases is excluded from the 57 Fe Mössbauer spectroscopy measurements. Temperature dependent dielectric constant measurements show the relaxation behaviour in highly doped samples.